2000
DOI: 10.1034/j.1600-0420.2000.078002182.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinal detachment after silicone oil removal

Abstract: ABSTRACT.Purpose: To evaluate the causes of retinal detachment after silicone oil removal, to define possible risk factors and the anatomical and functional prognosis of this complication. Methods: 112 eyes that underwent silicone oil removal were included. The group of eyes with retinal detachment after oil removal (18/112 eyes, 16.1%) was compared with the group with no postoperative retinal detachment. Results: The most common cause for retinal detachment after oil removal was anterior PVR (77.8%). Initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 13 publications
5
40
1
8
Order By: Relevance
“…Other investigators have suggested that preoperative risk factors may indicate a higher risk of failure after silicone oil removal, for example, anterior PVR 13 and multiple procedures with oil in situ before removal. 14 However, perhaps due to the small number of patients, preoperative risk factors did not reach a significant level of predictability.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have suggested that preoperative risk factors may indicate a higher risk of failure after silicone oil removal, for example, anterior PVR 13 and multiple procedures with oil in situ before removal. 14 However, perhaps due to the small number of patients, preoperative risk factors did not reach a significant level of predictability.…”
Section: Discussionmentioning
confidence: 99%
“…Eyes with macular detachment usually had a bad visual outcome. Other factors, such as complications and multiple operations, may also correlate with a bad visual outcome [10, 11, 16]. In seeking anatomic success for recurrent retinal detachments, both surgeons and patients should be aware of the high possibility of unfavourable visual results.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal detachment occurred at various frequencies after silicone oil removal [5, 6, 7, 8, 9], but the treatment and results of retinal detachment following silicone oil removal were not well documented [10, 11]. In the present paper, we summarize our management and the outcome of retinal detachment after silicone oil removal.…”
Section: Introductionmentioning
confidence: 99%
“…In der dritten, der europaischen Daunomycin-Studie sind keine Angaben uber die Silikonolentfernung zu finden [3]. Seit 1995 gab es eine Reihe von Berichten nber Silikonolentfernungen, die jedoch wegen der niedrigen Fallzahl oder wegen der gemischten Atiologie hier nur zurn Teil in die Diskussion einbezogen werden konnen [9][10][11][12][13][14][15][16][17][18][19][20][21]. Jonas [12] fand, dass eine Ursache der Reablation nach Silikonolentfernung die unvollstandige Entfernung der Glaskorperbasis ist.…”
Section: Diskussionunclassified
“…Das Ende der Beobachtungszeit haben wir auf 6 Monate postoperativ festgelegt, da bereits nachgewiesen wurde, dass Reablationes jenseits dieser Zeitgrenze auBerst selten sind [17,19,20,21]. Die funktionellen Resultate in unserer Studie entsprechen denen von Coll [6] and bestatigen auch die Ergebnisse von Scott [2] die nachwiesen, dass ein besserer Endvisus erreicht wird, wenn eine rasche anatomische Heilung erfolgt.…”
Section: Diskussionunclassified